Localized Castleman's disease presenting as a vascular right iliac fossa mass - Abdullah, Khairul Muhsein; Liew, Ngoh Chin; Al-Azawi, Abd Al-Rhman Hikmet Shaker; Abdul Wahab, Shahrin Iskandar (Elsevier, 2004)
Castleman's disease is a rare lymphoproliferative disorder of unknown aetiology. The presentation is varied, diagnosis is difficult, and optimum management is still unknown. We report our experience with a case of Castleman's disease in a 34-year-old woman who presented with pallor, hepatosplenomegaly, and a right iliac fossa mass that was 5 cm in diameter. This was initially diagnosed as a soft tissue sarcoma and preoperative tumour embolization was planned before excision. Mesenteric arteriogram revealed that the feeder arteries arose from the superior mesenteric artery and embolization was aborted for fear of causing bowel ischaemia. On laparotomy, lymphoid enlargement was found between the leaves of the jejunal mesentery. The tumour was relatively avascular and the overlying mesenteric vessels contributed to the duplex ultrasound and computerized tomography appearance of hypervascularity. The tumour with the mesentery and the overlying segment of jejunum was excised completely. Histopathology confirmed Castleman's disease. The purpose of this report is to present this rare case that caused a diagnostic dilemma and to review the management of this disorder.